Mechanochemical Knoevenagel condensation investigated in situ - Haferkamp, Sebastian; Fischer, Franziska; Kraus, Werner; Emmerling, Franziska (Beilstein Journal of Organic Chemistry, 2017)
The mechanochemical Knoevenagel condensation of malononitrile with p-nitrobenzaldehyde was studied in situ using a tandem approach. X-ray diffraction and Raman spectroscopy were combined to yield time-resolved information on the milling process. Under solvent-free conditions, the reaction leads to a quantitative conversion to p-nitrobenzylidenemalononitrile within 50 minutes. The in situ data indicate that the process is fast and proceeds under a direct conversion. After stopping the milling process, the reaction continues until complete conversion. The continuous and the stopped milling process both result in crystalline products suitable for single crystal X-ray diffraction.
Keywords: ball milling; C–C coupling; in situ; Knoevenagel condensation; mechanochemistry